Data-Processing Strategies for Crossed-Strip Gamma-Ray Detectors - Durko, Heather L. (IEEE Nucl Sci Symp Conf Rec (1997), 2008)
Crossed-strip gamma-ray detectors are an attractive option for small-animal SPECT imagers due to their high space-bandwidth product. In systems with independent triggering of the two sides of the detector, advanced data-processing techniques are required to accurately determine gamma-ray interaction locations and energy deposition. Optimal detector operation further relies on rigorous detector characterization in order to achieve detector triggering uniformity and best timing resolution and to permit position and energy estimation with maximum-likelihood methods. We describe algorithms and methods developed for calibrating and characterizing a recently fabricated system based on 1024-strips-per-side 1-mm-thick silicon detectors.